The Principle of not Gathering Both Functions of Judging and Executing In the criminal field: Une étude comparative - SATOUH, Hamza; BOUSELSAL, Noureddine (Journal of Human Sciences, 2020)
The principle of not gathering functions is set up for protecting the individual freedom, it ensures the good conduct of penal case, as it is the principle dividing the functions between the different efficient judiciary authorities in the case (The pursuit, instruction, Judgment, Execution) in order to ensure no biasing and embodying the essence of impartiality in its subjective concept. However a recent polemic is raised about the opposition of gathering functions and the individual freedoms, At the comparison of the function of punitive execution to the other criminal functions (Pursuit, instruction, Judgment) especially when the sentence enforcement judge tries to amend the content of the judgment or the decision by issuing some decisions (release license, temporary suspension of the application of sanction, conditional liberation; "parole") or trying to amend the sanction limits (amending or canceling the security measure by the judge, or determining the date of its expiration by the sentence enforcement judge ) we find that it is slightly affected by the principle of separating the functions of the criminal Judiciary, although we find out that the theory of gathering is incarnated according to many cases and theses.